Determinação do d13C para avaliar a origem do CO2 de vinhos e espumantes - Leonardelli, Susiane (My University, 2016)
The increasing in sparkling wine production and consumption is visible, many countries are promising to make this product and the Brazil has been highlighted internationally by presenting excellent quality sparkling wine. In this study a method was validated and established to evaluate the CO2 origin from the sparkling wines, through the CO2 δ13C determination, by isotope ratio mass spectrometry, aiming the control adulteration with industrial carbon dioxide (CO2). The δ13C characterization was based in the isotopic difference from the photosynthetic cycles of the plant that originated the product. Five industrial CO2, six carbonated water, 39 still wine (wine without apparent CO2) and 59 commercial sparkling wine were analyzed. Furthermore, an experiment with a Chardonnay base wine was realized to verify the δ13C isotopic variation from the beginning (base wine) and the final (sparkling wine) after the second fermentation. It was observed that the CO2 δ13C is selective for the sparkling wine production method, presenting difference among the traditional, tank and Asti (Moscatel) sparkling wine. Values more negative for CO2 δ13C from industrial CO2 were found, distinguishing the natural CO2 from still wine, allowing establish a limit of control between -25‰ to -20‰ for the Moscatel sparkling. Through the experiment realized, with the wine and sparkling wine from the same grape, could be verified that occurred CO2 δ13C isotopic variation of approximately 45% from the beginning (-22,2‰) to the final (-12,3‰) of the fermentation. With this parameters it was possible to estimate the control limit of -14‰ for the sparkling wine produced by traditional method, values bellow suggest carbonation. Six commercial sparkling wine showed evidence of adulteration, with industrial CO2 addition, and three Moscatéis sparkling presented results out of the highest control limit, in this Moscateis was found the sugar cane addition beyond that permitted by the Brasilian law. Therefore it was concluded that the method is appropriate and accurate for CO2 13C determination and it was possible to establish a method to evaluate the CO2 origin with limits estimates to Moscatéis and sparkling wine elaborated by the traditional method.
O aumento da produção e consumo de espumante é notório, são muitos países promissores na elaboração deste produto e o Brasil tem se destacado internacionalmente por apresentar espumantes de excelente qualidade. Neste trabalho foi validada e estabelecida uma metodologia para avaliar a origem do CO2 dos vinhos espumantes, através da determinação do 13C do CO2, por espectrometria de massa de razão isotópica, visando o controle da adição ilegal de dióxido de carbono (CO2) industrial. A caracterização do δ13C foi baseada na diferença isotópica do ciclo fotossintético da planta que originou o produto, levando em consideração o processo de elaboração do espumante. Foram analisadas 5 amostras de CO2 industrial, 6 amostras de água gaseificada artificialmente, 39 amostras de vinhos tranquilos (vinho sem CO2 aparente) e 59 amostras de espumantes comerciais. Além disso, foi realizado um experimento com uma amostra de vinho base Chardonnay para verificar a variação isotópica do δ13C inicial (vinho base) e final (espumante). Observou-se que o δ13C do CO2 é seletivo quanto ao método de elaboração do vinho espumante, apresentando diferença entre os métodos tradicional, tanque e Asti (Moscatel). Foram encontrados valores mais negativos para δ13C do CO2 industrial diferenciando do CO2 natural dos vinhos tranquilos, permitindo estabelecer um limite de controle entre -25‰ e -20‰ para os espumantes Moscatéis. Através do experimento realizado, com vinho e espumante da mesma cultivar (Chardonnay), foi verificada uma variação isotópica de aproximadamente 45% do δ13C do CO2 inicial (-22,2‰) para o final (-12,3‰) da fermentação. Com estes parâmetros foi possível estimar o limite de controle de -14‰ para espumantes elaborados pelo método tradicional, sendo que, valores abaixo do estimado sugerem carbonatação. Seis amostras de espumantes comerciais das 59 analisadas apresentaram indícios de adulteração, com adição de CO2 industrial e 3 espumantes Moscatéis apresentaram adição de açúcar de cana além do permitido em lei no Brasil. Desta forma, concluiu-se que o método é confiável e preciso para determinação de 13C do CO2 e foi possível caracterizar uma metodologia para avaliar a origem do CO2, com limites estimados para espumantes elaborados pelo método tradicional e Moscatel.
Keywords: Vinhos espumantes; Dióxido de carbono; Biotecnologia; Sparkling wines; Carbon dioxide; Biotechnology